Diazotroph Genomes and Their Seasonal Dynamics in a Stratified Humic Bog Lake - Fernandez, Leyden; Peura, Sari; Eiler, Alexander; Linz, Alexandra M.; McMahon, Katherine D.; Bertilsson, Stefan (Frontiers in Microbiology, 2020)
Aquatic N-fixation is generally associated with the growth and mass development of Cyanobacteria in nitrogen-deprived photic zones. However, sequenced genomes and environmental surveys suggest active aquatic N-fixation also by many non-cyanobacterial groups. Here, we revealed the seasonal variation and genomic diversity of potential N-fixers in a humic bog lake using metagenomic data and nif gene clusters analysis. Groups with diazotrophic operons were functionally divergent and included Cholorobi, Geobacter, Desulfobacterales, Methylococcales, and Acidobacteria. In addition to nifH (a gene that encodes the dinitrogenase reductase component of the molybdenum nitrogenase), we also identified sequences corresponding to vanadium and iron-only nitrogenase genes. Within the Chlorobi population, the nitrogenase (nifH) cluster was included in a well-structured retrotransposon. Furthermore, the presence of light-harvesting photosynthesis genes implies that anoxygenic photosynthesis may fuel nitrogen fixation under the prevailing low-irradiance conditions. The presence of rnf genes (related to the expression of H+/Na+-translocating ferredoxin: NAD+ oxidoreductase) in Methylococcales and Desulfobacterales suggests that other energy-generating processes may drive the costly N-fixation in the absence of photosynthesis. The highly reducing environment of the anoxic bottom layer of Trout Bog Lake may thus also provide a suitable niche for active N-fixers and primary producers. While future studies on the activity of these potential N-fixers are needed to clarify their role in freshwater nitrogen cycling, the metagenomic data presented here enabled an initial characterization of previously overlooked diazotrophs in freshwater biomes.